2001
DOI: 10.2169/internalmedicine.40.1132
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hypersensitivity Pneumonitis Induced by Shiitake Mushroom Spores Associated with Lung Cancer.

Abstract: A 61-year-old man was admitted to our hospital with a 6-month history of productive cough. He, along with his wife, had been involved with Shiitake mushroomcultures for a period of 12 years. On admission, chest radiography showed bilateral fine-nodular shadowand CTscans showed reticulonodular opacities and a ground-glass appearance predominantly in the subpleural area in both lungs, and a mass in the left S6. Resected pathological specimens obtained by left lower lobectomy revealed lung adenosquamous carcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…But also, workers who are not as highly exposed to dusts have been reported to develop chronic cough. For instance, vegetable pickers [ 82 ] or greenhouse workers [ 83 ] were reported to have higher prevalences of chronic cough and also workers who process mushrooms [ 84 - 86 ].…”
Section: Introductionmentioning
confidence: 99%
“…But also, workers who are not as highly exposed to dusts have been reported to develop chronic cough. For instance, vegetable pickers [ 82 ] or greenhouse workers [ 83 ] were reported to have higher prevalences of chronic cough and also workers who process mushrooms [ 84 - 86 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ta-ble 1 details and reviews several species and antigens which have not been previously reported as causal agents of MWL [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25]. Of note is the case report of HP in a 61-year-old Japanese man [7] who was exposed for 12 years to Shiitake mushrooms and then developed an adenosquamous carcinoma lesion (stage 1B) in his left lung. Such a report as this is of concern in that there are still little indications as to the long-term effects of some of the newly introduced cultivars, in terms of their potential to develop lung disease other than HP.…”
Section: Introductionmentioning
confidence: 99%
“…rectivirgula , W . sebi , Aspergillus and E. amstelodami may be helpful for potentially excluding more commonly inciting antigens if negative [ 42 45 , 94 ]. Otherwise, a history of farm exposure on its own may be insufficient to confirm HP diagnosis or assist in antigen avoidance.…”
Section: Discussionmentioning
confidence: 99%